Crosstalk Between Apoptosis and Autophagy: Environmental Genotoxins, Infection, and Innate Immunity. (17th February 2017) - Kemp, Michael G
Autoimmune disorders constitute a major and growing health concern. However, the genetic and environmental factors that contribute to or exacerbate disease symptoms remain unclear. Type I interferons (IFNs) are known to break immune tolerance and be elevated in the serum of patients with autoimmune diseases such as lupus. Extensive work over the past decade has characterized the role of a protein termed stimulator of interferon genes, or STING, in mediating IFN expression and activation in response to cytosolic DNA and cyclic dinucleotides. Interestingly, this STING-dependent innate immune pathway both utilizes and is targeted by the cell's autophagic machinery. Given that aberrant interplay between the apoptotic and autophagic machineries contributes to deregulation of the STING-dependent pathway, IFN-regulated autoimmune phenotypes may be influenced by the combined exposure to environmental carcinogens and pathogenic microorganisms and viruses. This review therefore summarizes recent data regarding these important issues in the field of autoimmunity.